Benign cystic peritoneal mesothelioma: an abdominal daze - Aravind, R. M.; Narayanasamy, Sangara Narayanan (International Journal of Advances in Medicine, 2017)
Benign cystic peritoneal mesothelioma (BCPM) is a rare clinical entity with varied presentations. Its obscure etiology and association with various intraabdominal conditions makes a precise diagnosis difficult. Diagnostic accuracy and diligent follow-up are essential because, though benign nature, it recurs locally. Herewith reporting a case of BCPM presenting as acute abdomen.